Effect of ball milling time on the microstructure and compressive properties of the Fe-Mn-Al porous steel - Xie, Lingzhi; Xu, Zhigang; Qi, Yunzhe; Liang, Jinrong; He, Peng; Shen, Qiang; Wang, Chuanbin (International journal of minerals, metallurgy and materials, 2023)
In the present work, Fe-Mn-Al-C powder mixtures were manufactured by elemental powders with different ball milling time, and the porous high-Mn and high-Al steel was fabricated by powder sintering. The results indicated that the powder size significantly decreased, and the morphology of the Fe powder tended to be increasingly flat as the milling time increased. However, the prolonged milling duration had limited impact on the phase transition of the powder mixture. The main phases of all the samples sintered at 640°C were α-Fe, α-Mn and Al, and a small amount of Fe 2 Al 5 and Al 8 Mn 5 . When the sintering temperature increased to 1200°C, the phase composition was mainly comprised of γ-Fe and α-Fe. The weight loss fraction of the sintered sample decreased with milling time, i.e., 8.3wt% after 20 h milling compared to 15.3wt% for 10 h. The Mn depletion region (MDR) for the 10, 15, and 20 h milled samples was about 780, 600, and 370 µm, respectively. The total porosity of samples sintered at 640°C decreased from ∼46.6vol% for the 10 h milled powder to ∼44.2vol% for 20 h milled powder. After sintering at 1200°C, the total porosity of sintered samples prepared by 10 and 20 h milled powder was ∼58.3vol% and ∼51.3vol%, respectively. The compressive strength and ductility of the 1200°C sintered porous steel increased as the milling time increased.